Spider Diversity in Bamboo Clumps on Mount Pangilun, Padang City - Aprilya, Rara; Satria, Rijal; Pratama, Sandi Fransisco (Jurnal Biologi Tropis, 2025)
Bamboo in Indonesia grows in clumps that create habitats that support biodiversity that can be studied through bioindicators, such as spiders that act as biological control agents as well as indicators of ecosystem diversity. This research was carried out with the aim of determining the diversity of spiders in bamboo clumps. The spider collection method is Hand Collecting and Beating. The results of the study found 14 species from 14 genera, 10 spider families consisting of 38 individuals. The species with the highest number of individuals is Ctenus hibernalis which reaches 14 individuals, while most other species only have a number of individuals between 1 to 3. This variation in the number of individuals per species is likely due to factors such as habitat differences, spider behavior, and the effectiveness of each collection method.